Effect of Histidine on Sensetivity of Some Pathogenic Bacteria. - Al-Jabar, Fatima A Abd; Ahmed, Ali S (Al-Nahrain Journal of Science, 2018)
The purpose of this study was to determine the antibacterial effect of the amino acid histidine against two pathogenic bacteria Escherichia coli and Staphylococcus aureus. No antibacterial activity was observed for histidine at all tested concentrations. The sensitivity test for E.coli and S. aureus was performed against ten types of antibiotics. The antibiotics used for E.coli were Levofloxacin(Lev), Streptomycin(S), Rifampicin(Rp), Metronidazole(Mz), Cloxacillin(Cx), Ciprofloxacin(Cip), Tetracycline(T), Nalidixic acid(Na), Penicillin(P) and Vancomycine(Va) and the results of inhibition zones were 44, 14,8, 0,0, 35, 24, 28, 16 and 14 mm respectively. When the Histidine added at concentration 10 mg/ml to Mueller hintone agar, the inhibition zones became 24, 12, 18, 0, 0, 24, 32, 25, 13 and 14 mm for each antibiotic respectively. The antibiotics used forStaph. aureus areLevofloxacin (Lev), Gentamicin(Gm), Rifampicin(Rp), Metronidazole(Mz), Cloxacillin(Cx), Ciprofloxacin(Cip), Tetracycline(T), Clarithromycin(Cla), Vancomycine (Va) and Chloramphenicol (C). Result of inhibition zones were 40, 30, 0, 0, 0, 22, 10, 0, 10 and 22 mm when the Histidine added at concentration 10 mg/ml to the mueller hinton agar, the inhibition zones became 30, 20, 16, 0, 0, 26, 15, 0, 10 and 22 mm. Applicable experiment of the histidine effect was conducted on resistant and sensitive isolates against Histidine of Mycobacterium tuberculosis (TB) in Pulmonary Institute in Baghdad. It was found that mixing of Histidine with Rifampicin changed the response of resistant isolate against Rifampicin and turned into sensitive. This results may encourage mixing antibiotics and Histidine instead of using the more effective and harmful antibiotics against the resistant isolates.